Swings and roundabouts: The impact of legal drafting on the language and understanding of copyright law and the need for educational materials†. Issue 3 (1st September 2016) - Bosher, Hayleigh; Mendis, Dinusha
Abstract : Legislators face the challenging task of drafting copyright law, which takes into account the views of various stakeholders, intended policy and technological developments, whilst ensuring that the wording and language that is used is accurate and precise. Meeting these objectives means that the law in its legislative form can be hard-to-understand, complex and not easily accessible to the layperson. This article explores steps, which have been put in place by various organisations and online resources, to assist in the understanding of copyright for the public and schools, with particular focus on education and teaching materials – as presented on Copyrightuser.org.